Studying Human Relatedness through a Shared Gaming Experience. (September 2015) - Cunningham, Rachel; Alex, Leo; Frederick, Christina; Via, Christopher; Kring, Jason
The importance of relatedness in collocated multiplayer video games should not be underestimated. Interpersonal relationships, which develop from social interactions that occur during gameplay, contribute to player motivation and meaningful and memorable experiences for the players. In this study we examined how interpersonal touch within a gameplay experience impacted player motivation and inter-player impressions. Dyads played one of two iPad-based games in three different conditions, one of which required physical contact between the players. Results indicated those in the touch-based conditions scored higher on several measures of intrinsic motivation and impressions of their teammate.